STRATEGIES IN TRANSLATING LIVE METAPHORS - Amalia, Desthia (Journal of Language and Literature, 2017)
This research discusses strategies in translating live metaphors on Dan Brown’s novels and translations in Indonesian. The aims of the research are to find out what live metaphors used in Dan Brown’s novels, to identify how live metaphors translated into Indonesian, to find out the principles are used in translating live metaphors, to find out the strategies that are used in translating live metaphors, to find out the most dominant strategy that is used in translating live metaphors. The method employed in this research is qualitative. The findings revealed that there are 75 live metaphors found in Dan Brown’s novels. 24 data were translated from metaphor into metaphor, 20 data were translated literally, 17 data were translated from metaphor into simile, 4 data have changed in sentence structure, 2 data translated by having expansion, 2 data were translated implicitly, 2 data were translated explicitly, 1 datum has changed in phrase structure, 3 data have changed in clause structure, 1 datum translated by having transposition. Those data are analyzed based on principle of translation: 40 data used idiom, 28 data used meaning, and 7 data used form principle.  Moreover the strategies which found out as follows :40 data (52%) used trope change (semantic strategy), 20 (27%) data used literal (syntactic strategy), 4 (6%) data used sentence structure change (syntactic strategy), 2 (3%) data used distribution change (semantic strategy), 4 (6%) data used explicitness change (pragmatic strategy), 1 (1%) datum used phrase structure change (syntactic strategy), 3 (4%) data used clause structure change (syntactic strategy), 1 (1%) datum used transposition (syntactic strategy).  According to the data analysis, the most dominate strategy is trope change. Keywords: Strategies, Translation, Live metaphors